Neotectonic reactivation of the western section of the Malargüe fold and thrust belt (Tromen volcanic plateau, Southern Central Andes) - Sagripanti, Lucía (2015)
This study examines the neotectonic deformation and development of the Tromen massif, a Quaternary retroarc volcanic field located in the western section of the Malargüe fold and thrust belt in the Southern Central Andes. The linkages between neotectonic deformation in the intra-arc zone and the recent retroarc structures of the Tromen volcanic plateau are not clearly understood. These retroarc deformations affect the mid-section of the fold and thrust belt, leaving to the east a 200 km-wide deformed zone that can be considered inactive over the last 12–10 Ma. This out-of-sequence deformation west of the orogenic front area has not been previously addressed in detail. In this study, exhaustive mapping is used to describe and discriminate structures with a neotectonic component from those fossilized by Pleistocene strata. Two balanced cross-sections are constructed showing the distribution of the youngest deformations and their relation to pre-Miocene structures. An important means for evaluating this is the morphometric and morphological analyses that allowed identification of perturbations in the fluvial network associated with active structures. In a broader perspective, neotectonic activity in the fold and thrust belt is discussed and inferred to be caused by local mechanical weakening of the retroarc zone, due to injection of asthenospheric material evidenced by magnetotelluric surveys. Thus, deformation imposed by the oblique convergence between South American and Nazca plates, while to the south being limited to the Liquiñe-Ofqui fault system that runs through the arc zone, in the retroarc area is located at the site of magmatic emplacement, presumably in association with a thermally weakened-upper crust. This control exemplifies the relationship that exists between surficial processes, magmatic emplacement and upper asthenospheric dynamics in the Southern Central Andes.